MENINGKATKAN PENGUASAAN KONSEP RELASI DAN FUNGSI MELALUI PENDEKATAN SAINTIFIK PADA SISWA SMP KELAS VIII DI KOTA BANDUNG - Puja Ilham Purnama Sari; Tina Rosyana; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study intends to investigate and learn about the improvement of mastery of the concept of Relations and Functions in Grade VIII students of SMP Negeri 28 Bandung. The hypothesis of this research action is that via scientific approach, the mastery of the idea of Relation and Function of Grade VIII Students of SMP Negeri 28 Bandung may be improved. With a total of 32 students, this study was conducted on grade VIII students at SMP Negeri 28 Bandung in the 2020/2021 school year. The instrument utilized is a learning outcomes test that assesses students' mathematical concept skills. Initial tests (before action), cycle I and cycle II tests (after actions), and observation sheets for teachers and students are all examples of testing. Planning, action implementation, observation and assessment, and reflection are all part of this study approach. The data processing technique in this study is to find the average value by using Microsoft Excel. Cycle I's average test score was 73.86, up 18.21 points from the average beginning test result of 55.65. The average score of cycle II test results was 82.45, up 26.8 points from the average initial test result and 8.59 points higher than cycle I test results. The mastery of the idea of Relationships and Functions in grade VIII students of SMP Negeri 28 Bandung can be improved using a scientific method, according to work indicators.